2019
DOI: 10.1186/s13075-019-1977-9
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viral infections and the risk of rheumatoid arthritis

Abstract: Background We aimed to investigate the effects of ambient respiratory viral infections in the general population on rheumatoid arthritis (RA) development. Methods Data of weekly incident RA (2012–2013) were obtained from the Korean National Health Insurance claims database, and those of weekly observations on eight respiratory viral infections were obtained from the Korea Centers for Disease Control and Prevention database. We estimated the percentage change in incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 33 publications
0
84
0
8
Order By: Relevance
“…In a Korean study of 24,117 newly diagnosed RA patients, published before the discovery of SARS-CoV-2, an increased risk of developing rheumatoid arthritis after infection with other coronaviruses or influenza was reported. For an increase of 1% of coronavirus-infected patients, a 9.2% increase in the incidence of RA in the following months was observed, especially in women and older patients ( 107 ). Whether, there is direct molecular mimicry between coronavirus and host antigens or whether coronaviruses activate other, yet unclear mechanisms leading to chronic autoimmunity has to be investigated further.…”
Section: Does Sars-cov-2 Increase the Risk Of Developing A Rheumatic mentioning
confidence: 98%
“…In a Korean study of 24,117 newly diagnosed RA patients, published before the discovery of SARS-CoV-2, an increased risk of developing rheumatoid arthritis after infection with other coronaviruses or influenza was reported. For an increase of 1% of coronavirus-infected patients, a 9.2% increase in the incidence of RA in the following months was observed, especially in women and older patients ( 107 ). Whether, there is direct molecular mimicry between coronavirus and host antigens or whether coronaviruses activate other, yet unclear mechanisms leading to chronic autoimmunity has to be investigated further.…”
Section: Does Sars-cov-2 Increase the Risk Of Developing A Rheumatic mentioning
confidence: 98%
“…It has been also reported that respiratory viral infections increase the incidence of rheumatoid arthritis (RA). To date, three viruses which increases the RA incidence significantly were identified, one of which is SARS-CoV-2 (Joo et al, 2019). The genes upregulated in RA pathway response to SARS-CoV-2 are provided in Supplementary Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…At the moment, no studies have investigated a potential relationship between respiratory viral infections and the development of OA, as described for parainfluenza and coronavirus and the incidence of rheumatoid arthritis. 30 Similarly, looking the other way round, there is no documented increased risk of respiratory infections for OA patients compared with the general population.…”
Section: Oa and Covid-19 Predisposing Comorbidities In Oa Patientsmentioning
confidence: 99%